Combustion Behaviour and Morphology of Phosphonium Montmorillonite Filled Polypropylene/Magnesium Hydroxide Composites - Yu1, Biao; Zeng1, Xian-Shen; Dai1, Guang-Jian; Cai1, Xiang; Lin2, Zhi-Dan; Zhang2, Xiu-Ju; Tan1, Shao-Zao; Liu1, Ying-Liang (Asian Journal of Chemistry, 2011)
In order to prove the combustion behaviour of phosphonium montmorillonite (P-MMT) filled polypropylene/magnesium hydroxide (PP/ MH) composites, samples of PP/MH, PP/MH/Na-MMT and PP/MH/P-MMT have been prepared by melt compounding using a corotating twin-screw extruder. Combustion experiments and thermogravimetric analysis were applied to determine the thermal properties of polypropylene composites, scanning electron microscope were used to study the microstructures of chars. The results show that the ignition time increased with the addition of P-MMT, but decreased with the addition of Na-MMT. SEM demonstrated that a suitable amount of P-MMT can promote formation of charred of layers in polypropylene composites.